ANALISIS DAMPAK PANDEMI COVID-19 TERHADAP JUMLAH RUMAH TANGGA MISKIN DI NAGARI KURAI TAJI KABUPATEN PADANG PARIAMAN - Dina Risnita; Jean Elikal Marna (UIN Mahmud Yunus Batusangkar, 2021)
This study aims to analyze and find out; The impact of the Covid-19 pandemic on the number of poor households in Nagari Kurai Taji, Padang Pariaman Regency. This study used qualitative research methods. Sampling in this study using purposive sampling technique with the number of informants as many as 21 people. The results of this study conclude that the impacts caused by the Covid-19 pandemic on the number of poor households in Nagari Kurai Taji, Padang Pariaman Regency, are: (1). Reduced income from the main household work, (2). Reduced assistance for household needs that are usually borne by children, (3). The difficulty of finding another job after losing the main job, (4). There is a decrease in the average household expenditure, (5). There is a change in the pattern of household consumption. The results of the research are expected to contribute to the policy makers as an effort to overcome poverty, and can be used as a reference for students or interested parties for further research materials.